Synthesis, characterization and potential sensing application of carbon dots synthesized via the hydrothermal treatment of cow milk - Kumar, Avinash; Kumar, Ishant; Gathania, Arvind K. (Scientific reports, 2022)
Carbon quantum dots (CQDs) were synthesized in this study by hydrothermally treating cow milk. The procedure is simple, non-hazardous to the environment, and does not necessitate the use of any special instruments or chemicals. CQDs were practically almost circular when they were manufactured and had an average size of 7 nm. Carbon (67.36%), oxygen (22.73%), and nitrogen (9.91%) comprised the majority of their composition. They feature broad excitation-emission spectra, excitation-dependent emission, and temperature-dependent photoluminescence. They remained quite stable in the presence of a lot of salt, UV radiation, and storage time. Because luminescence quenching mechanisms are sensitive to and selective for Sn 2+ , they can be employed to create a nanosensor for detecting Sn 2+ .